Gods in the Time of Democracy - Jain, Kajri (Book collections on Project MUSE., 2021)
"Kajri Jain examines how the monumental statues erected in India following its economic reforms in the 1990s became a favored religious and political form with which to assert cultural, political, religious, and caste power."--